2016
DOI: 10.3390/toxins8110310
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Characterization, and Mycotoxin Production Ability of Fusarium Species on Korean Adlay (Coix lacrymal-jobi L.) Seeds

Abstract: Adlay seed samples were collected from three adlay growing regions (Yeoncheon, Hwasun, and Eumseong region) in Korea during 2012. Among all the samples collected, 400 seeds were tested for fungal occurrence by standard blotter and test tube agar methods and different taxonomic groups of fungal genera were detected. The most predominant fungal genera encountered were Fusarium, Phoma, Alternaria, Cladosporium, Curvularia, Cochliobolus and Leptosphaerulina. Fusarium species accounted for 45.6% of all species foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Alternatively, the number of genes may be related to the amount of toxin, and the method of estimate the toxin can affect the amount of poison 39 . Previous study also showed that the rate of production of toxins on oilseeds crops (exceeding 300 ppb) was more than the production it on grain 22 .…”
Section: The Concentration Of Mycotoxins In Cropsmentioning
confidence: 91%
See 2 more Smart Citations
“…Alternatively, the number of genes may be related to the amount of toxin, and the method of estimate the toxin can affect the amount of poison 39 . Previous study also showed that the rate of production of toxins on oilseeds crops (exceeding 300 ppb) was more than the production it on grain 22 .…”
Section: The Concentration Of Mycotoxins In Cropsmentioning
confidence: 91%
“…According to the above-mentioned studies 16,18,19,22 , frequency and sovereignty indicators illustrate that some species in the environment have been confirmed and replicated, such as Aspergillus, Fusarium, and Penicillium, despite the different environmental conditions of each study. This evidence shows the extent of these species of fungi to tolerate the various environmental changes.…”
Section: Prevalence and Frequency Of Fungi Producing Toxinsmentioning
confidence: 96%
See 1 more Smart Citation
“…Fusarium and Alternaria are notorious for their mycotoxin-producing abilities, but few studies have focused on the mycotoxin production capacity of the two fungi isolated from herbal medicines. An et al [32] examined the mycotoxin production ability of the Fusarium species from Korean adlay seeds by ELISA analysis, and FUM and ZEN were the main mycotoxin products. However, the isolated Fusarium species produced only the acetyl forms of DON in our study, and no other mycotoxins were detected.…”
Section: The Isolated Fusarium and Alternaria Strains Are Capable Of ...mentioning
confidence: 99%
“…An antagonist test in vitro was conducted to determine the antagonistic activity of selected betel endophytic fungi against Fusarium pathogenic fungi. The antagonistic in vitro test was observed on the 10th day when the pathogen control hyphae had reached the edge of the petri dish [20]. The fungi used for the antagonist test were fungi that had passed the pathogenicity test, namely endophytic fungi with codes ES3, ES7, ES9, ES23, ES26, ES27, and ES28 [21].…”
Section: Endophytic Fungi Antagonist Test Against Pathogenic Fungi In...mentioning
confidence: 99%